SISTEM INFORMASI KEGIATAN KWARTIR RANTING MAOS(SIKEKWARMA) BERBASIS WEBSITE - Diva Nur Vadia; Cahya Vikasari; Antonius Agung Hartono; Agus Susanto; Prih Diantono Abda’u (Jurnal Riset Teknik Komputer, 2024)
The Kwartir Ranting Maos office manages the Scout Movement at the sub-district level. With 39 Scout units from siaga, penggalang, to penegak levels, there is a need for efficient activity report tracking and proposal submission, along with accountability reports for completed activities. Currently, these processes are done conventionally, requiring direct submissions from Scout units to Kwarran, making it challenging to monitor ongoing and scheduled activities. This study aims to design an administrative system to streamline these processes, making them more effective, efficient, and optimal. The research findings indicate that the SIKEKWARMA system can significantly enhance the management and supervision of Scout units by the Kwartir Ranting Maos. The system allows simultaneous access to information, facilitating better coordination among all involved parties. Additionally, it improves the accountability of proposal submissions and activity reports. Overall, SIKEKWARMA supports better decision-making and communication within the Kwartir Ranting Maos.